Analisis Beban Kerja Dalam Penentuan Tenaga Kerja Optimal Dengan Metode Workload Analysis dan Full Time Equivalent di Konveksi Gradatie Vendor - Abdurrahman, Afif; Roswandi, Iwan; Junaedi, Didi (Proceeding Mercu Buana Conference on Industrial Engineering, 2021)
Workload is one of the factors affecting employee performance. Sometimes employees have an overload, while other employees have an underload. This kind of problem also occurs with Gradatie Vendor Convection. The method used is full time equivalent (FTE) to find out the workload of each operator by changing the hours of the workload to the number of people needed to complete a particular job. From the results of the study, it was found that 8 operators have an underload workload. Optimization of labor performance can be carried out by changing the composition of the elements of the activities of each labor force or reducing the number of workers based on the calculation of Full Time Equivalent.